Infrastructure, Learning Complements, and Student Learning : Working Together for a Brighter Future - Sawamoto, Akiko (World Bank, Washington, DC, 2020)
The purpose of this mixed methods study was twofold: (i) to examine how school infrastructure and learning complements can be better utilized to promote student learning in Indonesian schools; and (ii) to help the relevant ministries make more informed decisions about investment in school infrastructure and learning complements. Three analyses were conducted in the quantitative component: descriptive and comparative analyses of madrasah infrastructure, and a multivariate analysis of madrasah infrastructure and student achievement. The qualitative component employed the intentional sampling and positive‐deviance approach consisting of semi‐structured phone interviews with principals, teachers, librarians, and parents from 20 madrasah and non‐madrasah schools (11 high‐performing secondary schools with science laboratories and nine primary schools with libraries of which eight were supported by the innovation for Indonesia’s school children program, which aims to improve students’ literacy and numeracy skills). The results of the descriptive and comparative analyses indicated that the madrasah sector as a whole is not adequately equipped with basic physical and learning resource infrastructure and that private madrasahs have significantly lower levels of infrastructure than their public counterparts. However, the multivariate analysis results did not conclusively show that infrastructure directly contributes to student learning outcomes. The qualitative analysis found some promising learning practices related to teachers’ professional development, literacy initiatives, and customized teaching and learning. Nevertheless, challenges remain for many schools in the disconnect between pedagogical and infrastructural quality assurance mechanisms, the failure to fully exploit libraries as resources for student learning, and learning spaces and assets that are not sufficiently conducive to science education. Based on the study results and findings, this report offers four key steps to address the main challenges related to school infrastructure and learning complements: (i) prioritize resource allocation to basic physical and digital infrastructure for the most underserved groups of students; (ii) leverage educators to maximize their potential as catalysts in facilitating improved teaching and learning processes through an innovative and effective utilization of learning spaces and complements; (iii) streamline and strengthen quality assurance mechanisms to document, monitor, and assess the quality, condition, and use of infrastructure and related assets, and to improve the links between school infrastructure management and learning quality management; and (iv) increase the overall resilience of the education system to future crises by strengthening its capacity to coordinate, monitor, and manage the continued delivery of equitable education services through distance and hybrid learning.